Current Trends in Particle Toxicology - Wells, Miles (United States : American Medical Publishers, 2021)
Particle toxicology focuses on understanding and describing the relationship between exposure to the agents and their capability to adversely affect human health. It also attempts to identify the underlying pathobiological mechanisms. Particle toxicology studies particle-induced hazards such as inhalation of particles which can cause oxidative stress. Nanoparticle toxicology is a subspecialty of particle toxicology. The research in the field of particle medicine focuses on nanoparticles which have unusual properties and have the potential for novel clinical applications. It finds applications in the areas of imaging and diagnostics, drug delivery, and anticancer therapy. This book elucidates the concepts and innovative models around prospective developments with respect to particle toxicology. Different approaches, evaluations, methodologies, and advanced studies on the topic have been included in it. Scientists and students actively engaged in this field will find this book full of crucial and unexplored concepts.
Includes index.
Includes bibliographical references.
Keywords: Toxicology; Particles -- Toxicology